2021
DOI: 10.12669/pjms.38.icon-2022.5778
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility pattern of Mycobacterium tuberculosis over a period of five years at Indus Hospital and Health Network, Karachi, Pakistan

Abstract: Objective: To determine the susceptibility pattern and frequency of isolation of multidrug, pre-extensively drug and extensively drug resistant TB in a tertiary care hospital in Karachi, Pakistan. Method: A cross-sectional study was designed. Samples received in the lab were processed for growth and sensitivity testing of Mycobacterium tuberculosis. Isolation of MTB was done on Mycobacteria growth indicator tube (MGIT) followed by identification using MPT64. Samples were than evaluated for drug sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Cultures were left for incubation for up to 42 days (10). Drug susceptibility testing was achieved by BACTEC MGIT 960 following the manufacturer's procedures (13). Reference strain H37RV (ATCC 27294) was used as a quality control of culture and drug susceptibility test, and the strain was sensitive to all standard anti-TB drugs (10).…”
Section: Microbiological Methodsmentioning
confidence: 99%
“…Cultures were left for incubation for up to 42 days (10). Drug susceptibility testing was achieved by BACTEC MGIT 960 following the manufacturer's procedures (13). Reference strain H37RV (ATCC 27294) was used as a quality control of culture and drug susceptibility test, and the strain was sensitive to all standard anti-TB drugs (10).…”
Section: Microbiological Methodsmentioning
confidence: 99%
“…Mycobacterium tuberculosis; an acid fast, alcohol fast, aerobic airborne bacterium is the reason behind such inevitable spreading of PTB. 1 PTB affected the one third population of world in which 33% population have active PTB. 1 World Health Organization (WHO) presented in their 2021 global tuberculosis report that 10.0 million new PTB patients were registered in 2020 throughout the world, among which majority were men.…”
Section: Introductionmentioning
confidence: 99%
“… 1 PTB affected the one third population of world in which 33% population have active PTB. 1 World Health Organization (WHO) presented in their 2021 global tuberculosis report that 10.0 million new PTB patients were registered in 2020 throughout the world, among which majority were men. More precisely 58 percent cases were male as compared to 32 percent female and 10% children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have advocated development of new strategies to reduce the spread of this disease. 4 Safety and efficacy of Remdesivir on mortality and length of stay in hospitalized Covid19 patients has been studied by Quratulain Shaikh et al, in this prospective cohort study which enrolled two hundred sixty eight patients. The findings of this study showed that there was no difference in inhospital mortality while length of stay was longer in these patents.…”
mentioning
confidence: 99%